2015
DOI: 10.1186/s12885-015-1303-0
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 is involved in miR-124-mediated suppressive effects on esophageal cancer cells

Abstract: AbstractsBackgroundEsophageal cancer (EC) is one of the most common cancers worldwide. The cancer-related inflammation pathway- signal transducer and activator of transition 3 (STAT3) signaling pathway has been reported to play critical role in its initiation and progression, while the way mediated its hyperactivation remains elusive so far. Accumulating studies reported the important role of microRNAs (miRNAs) in the regulation of gene expression, among of which, the miR-124/STAT3 interaction has been widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 31 publications
3
38
0
1
Order By: Relevance
“…This is consistent with a report by Zhang et al (2014c) who illustrated that miR-124 could increase the radiosensitivity of conditionally reprogrammed cells by blocking the expression of paired related homeobox 1 (PRRX1). It has also been shown that miR-124 expression is consistently suppressed in esophageal cancer tissues and cell lines, where it functions as a tumor suppressor (Cheng et al, 2015). Similar to their results, we found that the expression of miR-124 was downregulated in esophageal cancer tissues.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with a report by Zhang et al (2014c) who illustrated that miR-124 could increase the radiosensitivity of conditionally reprogrammed cells by blocking the expression of paired related homeobox 1 (PRRX1). It has also been shown that miR-124 expression is consistently suppressed in esophageal cancer tissues and cell lines, where it functions as a tumor suppressor (Cheng et al, 2015). Similar to their results, we found that the expression of miR-124 was downregulated in esophageal cancer tissues.…”
Section: Discussionsupporting
confidence: 90%
“…We also found that restoring miR-124a expression in ATL cells significantly decreases in vitro cellular proliferation and causes a significant reduction in tumor formation in vivo. Although miR-124 inhibition of STAT3 has been shown, 34 to our knowledge, this is the first study reporting miR-124a regulation of STAT3 in human leukemia/ lymphomas. Using a cancer profiler array along with in silico promoter analyses of genes downregulated by miR-124a, we identified STAT3 as a common regulator.…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies have suggested that lncRNAs serve as competing endogenous RNAs (ceRNAs) to sponge miRNAs, thereby regulating gene expression [19]. According to previous studies, miR-124 plays a suppressive role in cancers [20]. The role of miR-124 in bladder cancer was reported [21].…”
Section: Resultsmentioning
confidence: 99%